Enhanced phosphate removal from wastewater by using in situ generated fresh trivalent Fe composition through the interaction of Fe(II) on CaCO3. (1st September 2018) - Li, Yujie; He, Xiaoman; Hu, Huimin; Zhang, Tingting; Qu, Jun; Zhang, Qiwu
Abstract: Excessive existences of nutrients such as phosphate in the aqueous environment remain as a heavy concern although many researches have been reported for dealing with their removal. Based on the understanding toward the interactions of Fe compounds with phosphate and carbonate from many available researches, we designed a very simple and efficient approach for phosphate removal by using in situ generated fresh trivalent Fe composition through the interaction of Fe(II) as FeSO4 on CaCO3 . Addition and agitation of Fe(II) and CaCO3 simultaneously to phosphate solution allowed an amorphous Fe(III)-P or Ca-Fe(III)-P precipitation, with a phosphate removal rate close to 100%, to reduce the residual phosphorus concentration less than 0.03 mg/L from 100 mg/L, reaching the discharge limit, even with the addition amounts of CaCO3 as low as a stoichiometric ratio of CaCO3 /PO4 3− at 0.9 and ratio of Fe(II)/PO4 3− at 1.5, and the percent of P2 O5 in the precipitate was as high as 19.4% enough as phosphate source for fertilizer production. Different from the alkaline process with enough OH − group, the slow hydrolysis of CaCO3 resulting in low concentration of OH − group for the formation of Fe(OH)2, which was oxidized soon by air into trivalent Fe, achieved a continuous generation of fresh ferric composition for phosphate precipitation and could avoid its rapid formation and subsequent transformation into stable FeOOH of large particle size to lose the activity. These results based on the synergistic effect of using CaCO3 and Fe(II) together may have applications in the treatment of eutrophic wastewater through a process with many advantages of easy operation and low-cost besides the high removal efficiency with phosphate percentage inside the precipitate high enough to serve for fertilizer production. Graphical abstract: Highlights: Approach for phosphate removal through the interaction of Fe(II) on CaCO3 . Fe(II) could be oxidized by air in the surface of CaCO3 without adding any reagents. High efficiency of phosphate removal even at low concentration. The percent of P2 O5 in the precipitate was high enough for fertilizer production.